Recognizing and managing a deteriorating patient: a randomized controlled trial investigating the effectiveness of clinical simulation in improving clinical performance in undergraduate nursing students. (6th July 2015) - Stayt, Louise Caroline; Merriman, Clair; Ricketts, Barry; Morton, Sean; Simpson, Trevor
Abstract Aims To report the results of a randomized controlled trial which explored the effectiveness of clinical simulation in improving the clinical performance of recognizing and managing an adult deteriorating patient in hospital. Background There is evidence that final year undergraduate nurses may lack knowledge, clinical skills and situation awareness required to manage a deteriorating patient competently. The effectiveness of clinical simulation as a strategy to teach the skills required to recognize and manage the early signs of deterioration needs to be evaluated. Design This study was a two centre phase II single, randomized, controlled trial with single blinded assessments. Method Data were collected in July 2013. Ninety‐eight first year nursing students were randomized either into a control group, where they received a traditional lecture, or an intervention group where they received simulation. Participants completed a pre‐ and postintervention objective structured clinical examination. General Perceived Self Efficacy and Self‐Reported Competency scores were measured before and after the intervention. Student satisfaction with teaching was also surveyed. Results The intervention group performed significantly better in the post‐objective structured clinical examination. There was no significant difference in the postintervention General Perceived Self Efficacy and Self‐Reported Competency scores between the control and intervention group. The intervention group was significantly more satisfied with their teaching method. Conclusion Simulation‐based education may be an effective educational strategy to teach nurses the skills to effectively recognize and manage a deteriorating patient.